Investigation of the differences in designers’ spatial perception in interior spaces using Kokedama - Yerli, Ozgur; Sitemoglu, Aysu Esenturk (Edelweiss Applied Science and Technology, 2024)
The word kokedama consists of the Japanese words "koke" (moss) and "dama" (ball). Due to its easily accessible materials and easy construction, it has become an application that almost everyone can do, and its use is expected to become widespread. The aim of this study is to investigate the differences in the spatial perceptions of designers who have received basic design education in different faculties in the case of interiors that including kokedama. To measure the differences in spatial perception, photographs of 8 different public interiors were processed and a survey was administered to the subjects. The survey results were analyzed statistically. According to the results of the study, the increase in the value of the perceptibility and simplicity criteria also increases the value of other criteria. As the value of perceptibility and simplicity increases in kokedama applications, the perception of complexity decreases. This data explains that the use of kokedama contributes positively to spatial perception. The criteria that have the most effect when they are together are the structure/identity and perceptibility criteria. The highest scorers on the criteria affecting spatial perception were graduates of the faculty of fine arts, while the lowest scorers were graduates of the faculty of agriculture.